The role of a trauma review system and development of intra-operative checklists in improving the quality of fracture fixations in a high volume tertiary centre - Rajasekaran, RB; Jayaramaraju, D; Agraharam, D; Perumal, R; Kamal, A; Rajasekaran, S (Springer, 2020)
Introduction In high volume centres, audits are essential to ensure good surgical techniques and fracture fixations to avoid complications, revision surgeries and poor outcomes. A method to assess fixations for fractures of different regions employing different implants and surgical demands is a challenge. We present here a simple method of review and follow-up work flow of more than 6000 fixations every year that helped in improving outcomes and also provide training for residents and junior staff.